Treatment of De Novo Renal Transplant Recipients With Calcineurin Inhibitor–free, Belatacept Plus Everolimus–based Immunosuppression. Issue 2 (6th January 2023) - Peddi, V. Ram; Marder, Bradley; Gaite, Luis; Oberholzer, Jose; Goldberg, Ryan; Pearson, Thomas; Yang, Harold; Allamassey, Lisa; Polinsky, Martin; Formica, Richard N.
Abstract : Background: Compared with calcineurin inhibitor–based immunosuppression, belatacept (BELA)-based treatment has been associated with better renal function but higher acute rejection rates. This phase 2 study (NCT02137239) compared the antirejection efficacy of BELA plus everolimus (EVL) with tacrolimus (TAC) plus mycophenolate mofetil (MMF), each following lymphocyte-depleting induction and rapid corticosteroid withdrawal. Methods: Patients who were de novo renal transplant recipients seropositive for Epstein-Barr virus were randomized to receive BELA+EVL or TAC+MMF maintenance therapy after rabbit antithymocyte globulin induction and up to 7 d of corticosteroids. The primary endpoint was the rate of biopsy-proven acute rejection at month 6. Results: Because of an unanticipated BELA supply constraint, enrollment was prematurely terminated at 68 patients, of whom 58 were randomized and transplanted (intention-to-treat [ITT] population: n = 26, BELA+EVL; n = 32, TAC+MMF). However, 25 patients received BELA+EVL‚ and 33 received TAC+MMF (modified ITT population). In the ITT population, the 6-mo biopsy-proven acute rejection rates were 7.7% versus 9.4% in the BELA+EVL versus TAC+MMF group. The corresponding 24-mo biopsy-proven acute rejection rates were 19.2% versus 12.5% in the ITT population and 16.0% versus 15.2% in the mITT population; all events were Banff severity grade ≤IIA and similar between groups. One patient in each group experienced graft loss unrelated to acute rejection. The 24-mo mean unadjusted estimated glomerular filtration rates were 71.8 versus 68.7 mL/min/1.73 m 2 in the BELA+EVL versus TAC+MMF groups. Posttransplant lymphoproliferative disorder was reported for 1 patient in each group. No deaths or unexpected adverse events were observed. Conclusions: A steroid-free maintenance regimen of BELA+EVL may be associated with biopsy-proven acute rejection rates comparable to TAC+MMF.